A brief history of ELT Journal. (8th January 2021) - Smith, Richard
Abstract: This article traces the 75-year history of ELT Journal, using this as a means to cast light on trends in ELT over the same period and to acknowledge various sources of thought and practice. In the first part (1946–1971), the focus is on how the journal contributed to the establishment of a methodological orthodoxy which was relatively unaffected by academic applied linguistics but which drew sustenance, rather, from a tradition of theorized experience and practical linguistics dating back to pre-war times. In the second part (1971–1996), the focus is on tensions between this orthodoxy and newer 'communicative' ideas—still, though, with an emphasis on practical experience as well as academic insight, while the final phase (1996–2021) is viewed as being characterized, above all, by attempts to 'decentre' away from mainly UK-based expertise and towards an opening-up of professional discourse to previously neglected voices. Viewing the history of the journal in this manner reveals continuities as well as shifts in perception of how English should be defined, whose voices 'count' in the field, and of the value or otherwise of research and theory in relation to practical concerns.